Association of uterine activity and maternal volatile anesthetic exposure during open fetal surgery for spina bifida: a retrospective analysis. (May 2021) - Tra, S.; Ochsenbein-Kölble, N.; Stein, P.; Meuli, M.; Moehrlen, U.; Mazzone, L.; Kraehenmann, F.; Zimmermann, R.; Biro, P.
Highlights: Volatile anesthetic effect during fetal surgery investigated retrospectively. Minimum alveolar concentration (MAC) <2 and ≥2 compared. MAC <2 was not associated with an increased risk of uterine contractions. No fetal complications in either cohort. Higher MAC resulted in greater vasopressor usage. Abstract: Background: Recent warnings postulate a possible damaging effect of volatile anesthetics on the fetus. In our archive of fetal surgeries, we found wide variation in dosing of volatile anesthetics during spina bifida surgeries. We hypothesized that there was an association between volatile anesthetic exposure and uterine activity. Methods: Sixty anesthesia records from spina bifida operations were assessed. We analyzed the course of the administered volatile anesthetic during surgery and calculated from each patient's anesthesia record the volatile anesthetic exposure expressed in vol%h. We divided the records into two post hoc groups of the 20 lowest exposure (Group L) versus the 20 highest exposure (Group H), and compared them for uterine activity and fetal heart rate. Results: The number of contractions per hour was significantly greater in Group H (mean 1.3, SD ± 1.2) compared with Group L (mean 0.5, SD ± 0.6, P =0.049). There was no difference between the groups for the administration of the tocolytic drug atosiban ( P =0.29). The course of the mean arterial pressure did not significantly differ but group H needed significantly more vasoactive medication ( P <0.05). Conclusions: We found that a lower intra-operative volatile anesthetic exposure than recommended in the MOMS-trial (i.e. <2.0 minimum alveolar concentration [MAC]) was not associated with an increase in intra-operative uterine activity. This is an indication that during spina bifida surgery, 2.0 MAC may not be necessary to avoid potentially harmful uterine activity.